Sources of acute sport stress scale for sports officials: Rasch calibration - Anshel, M. H.; Kang, M.; Jubenville, C. (Psychology of Sport and Exercise, 2013)
Objectives: The purpose of this study was to develop and calibrate the Sources of Acute Stress Scale for Sports Officials (SASS-SO) using the Rasch model. Design and method: This was a cross-sectional, self-reported study. Of the 3300 participants with valid (no missing) data, 90.1% were males, ranging in age from 19.6 to 57.8 yrs., and serving as sports officials from 3 to 24 yrs. The officials represented high school, collegiate, and professional athletic associations representing 13 sports throughout the United States. Results: Using the Rasch model, the level of sources of stress item difficulty and individual's level of acute stress were estimated. Model-data fit was determined by Infit and Outfit statistics (=0.5 and =1.5). A rating scale was also evaluated for proper functioning. With the exception of two items, the model fit the data well. Infit and Outfit measures were within the appropriate range supported the unidimensional structure of the SASS-SO. The two most severe sources of acute stress were "I made an incorrect call" and "I was out of position." The two least severe sources of acute stress items were "I received verbal abuse from players" and "My supervisor/evaluator was present." Conclusions: The probability thresholds and item response ordering showed that the rating scale functioned well. Although item parameters had slightly inappropriate coverage, the ability parameters were reasonably varied. The results of this study support the use of the SASS-SO in assessing sources of acute stress among sports officials.